Experimental and advanced equilibrium studies on the enhanced adsorption of phosphate, cadmium, and safranin dye pollutants using methoxy exfoliated glauconite - Abukhadra, Mostafa R.; Fadl Allah, Aya; Shaban, Mohamed; Alenazi, Noof A.; Alqhtani, Haifa A.; Bin-Jumah, May; Allam, Ahmed A.; Bellucci, Stefano (Frontiers in Chemistry, 2024)
Natural glauconite, as a mixed-layered clay mineral, was subjected to exfoliation processes, producing silicate monolayers or individual sheets that were further modified with methanol into methoxy exfoliated glauconite (Mth/EXG). The structure was assessed as an enhanced adsorbent for three types of common water contaminants, including phosphate (PO 4 3-), safranin-O dye (SFR), and cadmium metal ions (Cd 2+ ). The Mth/EXG structure achieved promising adsorption capacities at the saturation points equal to 269.9 mg/g for PO 4 3-, 312 mg/g for SFR, and 234.5 mg/g for Cd 2+ which are significantly better than the reported values for several studied adsorbents of higher costs and complex production procedures. The adsorption processes and the predicted regulated mechanisms in terms of the adsorbate/adsorbent interface were illustrated based on the steric and energetic findings that correspond to the applied monolayer equilibrium model of one energy site. The structure displays active site densities of 82.5 mg/g (PO 4 3-), 136.3 mg/g (SFR), and 83.4 mg/g (Cd 2+ ), which illustrate the high uptake performance of SFR. Also, the steric parameters reflected the suitability of each existing site to be filled with 4 ions of PO 4 3-, SFR, and Cd 2+ . The adsorption energy (less than 40 kJ/mol) in conjunction with free adsorption energy from D-R model (8-16 kJ/mol) and steric parameters validate the dominant impact of the multi-ionic physical mechanisms (hydrogen bonding and van der Waals forces), in addition to the assistant impact of some weak chemical processes that might be assigned to the formed innersphere complex. Also, these reactions all occurred spontaneously with exothermic behaviors according to the thermodynamic functions. Additionally, the structure exhibit significant affinity for the studied pollutants even in the existing of completive chemical including anions, cations and organic molecules